ASPIP – AUTOMATIC AND ASSISTED DEFINITION OF ASSEMBLY SEQUENCES BASED ON COMPONENT LIAISONS AND SUBASSEMBLIES APPROACH - Viganò, R.; Osorio-Gómez, G. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
The design process of industrial products considers different aspects of the product lifecycle to make decisions about the functionality, manufacturability, usability, among other aspects related to the user interaction. Assembly sequence definition is an important phase of the product development process that is normally defined during the detailed design stage, and it is mainly based on skill and experience of manufacturing designers. The prospect to automatically identify possible assembly sequences at early stages of the design process, starting from contact or liaison information between components extracted from 3D CAD models would lead up to reduce time and costs, and would give interactive information for support designers during decision making activities. In this way, authors propose a computer application, so called Automatic Sequence Planner for Industrial Products (ASPIP), to automatically identify assembly sequences of an industrial product. The core of the application is based on an existent approach for Assembly Sequence Analysis, which is followed and presented step by step to enable the designer to create the assembly sequence. The tool enables the analysis of the liaison graph of the components of the product, which is automatically obtained from a kinematically stable CAD model, and automatically obtains a list of assembly sequences with at least one feasible sequence. The assembly sequence analysis of an industrial product is presented as a validation of the functionality of the application ASPIP.